2000
DOI: 10.1021/ja9937831
|View full text |Cite
|
Sign up to set email alerts
|

Protofilaments, Filaments, Ribbons, and Fibrils from Peptidomimetic Self-Assembly:  Implications for Amyloid Fibril Formation and Materials Science

Abstract: Deciphering the mechanism(s) of -sheet mediated self-assembly is essential for understanding amyloid fibril formation and for the fabrication of polypeptide materials. Herein, we report a simple peptidomimetic that self-assembles into polymorphic -sheet quaternary structures including protofilaments, filaments, fibrils, and ribbons that are reminiscent of the highly ordered structures displayed by the amyloidogenic peptides A , calcitonin, and amylin. The distribution of quaternary structures can be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
237
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(255 citation statements)
references
References 91 publications
(188 reference statements)
12
237
1
4
Order By: Relevance
“…The electron microscopy and fiber diffraction measurements suggest that the structural features of the fibrils formed from these peptides are similar to those described previously for disease-related amyloid structures. Furthermore, striking similarities are observed with fibrils formed from peptidomimetic compounds (48) and de novo designed peptides (49). It is interesting to note that our EM and fiber diffraction results are not in full agreement.…”
Section: Secondary Structure Of the Peptides In Their Fibrillar Statementioning
confidence: 86%
“…The electron microscopy and fiber diffraction measurements suggest that the structural features of the fibrils formed from these peptides are similar to those described previously for disease-related amyloid structures. Furthermore, striking similarities are observed with fibrils formed from peptidomimetic compounds (48) and de novo designed peptides (49). It is interesting to note that our EM and fiber diffraction results are not in full agreement.…”
Section: Secondary Structure Of the Peptides In Their Fibrillar Statementioning
confidence: 86%
“…48 Our model can naturally apply to the case of flat-ribbonlike amyloid fibrils, 19,22,[49][50][51] with possible extension to twisted ribbons 6,24,35,[50][51][52] or coiled helical structure with constant interacting regions ͓Fig. 6͑a͒ of Ref.…”
Section: Model and Simulation Algorithmmentioning
confidence: 99%
“…Langmuir monolayers of b-sheet peptides were, for example, reported to function as templates and serve as nuclei for the formation of inorganic nanocrystallites at the air-water interface. 12 Recently, numerous research groups have demonstrated that amphiphilic peptides self-assemble into b-sheet nanofiber architectures, [13][14][15][16][17][18][19][20] the surface of which has potential as a novel nanotemplate. [21][22][23] Several groups [24][25][26][27] have separately used b-sheet peptide nanofibers as templates to organize diacetylenes or dienes and promote their topochemical polymerization.…”
Section: Introductionmentioning
confidence: 99%